Magic Mike, Dirty Dancing, and the (Empty) Promise of Heteromasculinity - Tsai, Addie (The International Journal of Screendance, 2018)
In 1987, Eddie Murphy performed a comic sketch about white men dancing that would inform future movers and makers of white male dancing in American popular culture, helping to create a trope mocking white men for their inability to dance, most often referred to as the “white man dance.” At that time, Saturday Night Live, with the help of its host Patrick Swayze, fresh off the popularity of his work in sleeper hit Dirty Dancing, contributed to the trope itself with a sketch comparing the hypermuscular physique of Swayze vs. the flabby physique of comedian Chris Farley. Almost thirty years later, American popular culture would see a return to a renewed interest in the dance film with the stripper film Magic Mike. This article argues that although Magic Mike, like Dirty Dancing, relies on the makeover trope as its narrative and thematic engine, Magic Mike revises the popular dance film format to instead focus on the relationship between two men, Mike and Adam, rather than on a heterosexual partnering. Magic Mike’s focus on this male-to-male relationship inevitably comments on the exchange between heteronormative masculinity and compulsory heterosexuality and their assumed whiteness.